Foreign Direct Investment and Economic Stability: The case of Arab Peninsula - Al-Fawwaz, Abdulrahman A (Advances in Social Sciences Research Journal, 2018)
Abstract Purpose – The purpose of this research paper is to present the study regarding foreign direct investment and its relationship with economic stability. The case of Arab peninsula is discussed throughout the paper. Methodology – The secondary research design was selected and the exploratory study was conducted. The time series analysis was presented by exploring the FDI investment in Oman, Jordan, Saudi Arabia, Kuwait, Bahrain and Qatar. The data three-year data was collected by studying the FDI investment reports shared by Santander Trade. Findings – The findings of study presents the information regarding increase and decrease in FDI in countries from Arab Peninsula. The findings show that Qatar, Kuwait and Bahrain are able to accelerate their FDIs due to political and economic stability, but Saudi Arabia, Oman and Jordan are having downward FDI trend. Implications – This paper benefits academically and practically by providing the three years trend which can help investors to explore the favourable countries within Arab Peninsula for FDIs. On another side, the academic practitioners can utilize this study to conduct the future study by comparing least and most significant countries within Arab Peninsula for foreign investments.